Exosomes and cancer immunotherapy: A review of recent cancer research - Cao, Yue; Xu, Peng; Shen, Yangling; Wu, Wei; Chen, Min; Wang, Fei; Zhu, Yuandong; Yan, Feng; Gu, Weiying; Lin, Yan (Frontiers in Oncology, 2023)
As phospholipid extracellular vesicles (EVs) secreted by various cells, exosomes contain non-coding RNA (ncRNA), mRNA, DNA fragments, lipids, and proteins, which are essential for intercellular communication. Several types of cells can secrete exosomes that contribute to cancer initiation and progression. Cancer cells and the immune microenvironment interact and restrict each other. Tumor-derived exosomes (TDEs) have become essential players in this balance because they carry information from the original cancer cells and express complexes of MHC class I/II epitopes and costimulatory molecules. In the present study, we aimed to identify potential targets for exosome therapy by examining the specific expression and mechanism of exosomes derived from cancer cells. We introduced TDEs and explored their role in different tumor immune microenvironment (TIME), with a particular emphasis on gastrointestinal cancers, before briefly describing the therapeutic strategies of exosomes in cancer immune-related therapy.